If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1x = 74 Combine like terms: 3x + -1x = 2x 2x = 74 Solving 2x = 74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 37 Simplifying x = 37
| 9n-17=46 | | 16s^2-9=0 | | -29+77= | | -19+-24+-16+-13= | | 6s^2-30s+24=0 | | 6-(-18)= | | 50+x+x=500 | | 5x^8y^6+25x^6y^5+10xy=0 | | 120+x+x=600 | | 9x+16=12x-8 | | -4x+10f=2 | | 2x=w(5y-11) | | 5+2x=23-x | | -154+11= | | -28+4= | | d-5=-25 | | (x-5)z=4y | | 18+(-5)+(-5)+18= | | 3(x+32)=123 | | (8+3)*64= | | 8+3*64= | | s^2-16=0 | | a-5=23 | | =4y^2-4y-24 | | 4x-7=-21-10x | | 14=2t+48 | | 5g+4c+20=0 | | -0.77y=6 | | 2(3x+5)=6x+5 | | 4-6x=10-8x | | B+19=128 | | 2(3x+5x)=6x-7x |